2020
DOI: 10.1111/jphd.12386
|View full text |Cite
|
Sign up to set email alerts
|

Emergency department visits for nontraumatic dental conditions: a systematic literature review

Abstract: Objective: To summarize the literature on factors associated with emergency department (ED) use for nontraumatic dental conditions (NTDCs). Methods: Following a database search, empirical studies were included if they examined factors associated with ED visits for NTDCs. The factors identified in these studies were further categorized using the Andersen Behavioral Model. Where appropriate, odds ratios (ORs) predicting the likelihood of NTDC ED visits were extracted to obtain summary estimates using random effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 67 publications
1
21
0
Order By: Relevance
“…This is probably because toothache and dental abscesses are generally a complication of caries. As in other work, we found that people from Indigenous, poorer or rural backgrounds were generally at greater risk of all types of avoidable dental conditions 16–18 . There were similar findings for people with mental illness although this did not apply to all forms, the associations being non‐significant for periodontal disease and stomatitis.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…This is probably because toothache and dental abscesses are generally a complication of caries. As in other work, we found that people from Indigenous, poorer or rural backgrounds were generally at greater risk of all types of avoidable dental conditions 16–18 . There were similar findings for people with mental illness although this did not apply to all forms, the associations being non‐significant for periodontal disease and stomatitis.…”
Section: Discussionsupporting
confidence: 81%
“…As in other work, we found that people from Indigenous, poorer or rural backgrounds were generally at greater risk of all types of avoidable dental conditions. [16][17][18] There were similar findings for people with mental illness although this did not apply to all forms, the associations being nonsignificant for periodontal disease and stomatitis. This excess of presentations in psychiatric patients is consistent with findings of inequitable access to guideline-appropriate care for physical ill-health in general.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…In fact, uninsured adults are 3 times more likely to visit the emergency department for dental emergencies than privately insured adults. 5 Medicaid adult dental coverage varies significantly across states. According to a report from the Center for Health Care Strategies, 3 states have no adult dental coverage, 11 have emergency dental services only, 15 have limited dental benefit, and 20 states and Washington, DC, have extensive coverage under Medicaid.…”
mentioning
confidence: 99%